Blended learning and the language teacher: a literature review - Mendieta Aguilar, Jenny Alexandra (Colombian Applied Linguistics Journal, 2012)
An innovative idea which is increasingly gaining attention is the infusion of technology into face-to-face language curricular programs. Nonetheless, although “the approach of blending Computer-assisted Language Learning (CALL) applications with face-to-face teaching and learning is as old as CALL itself” (Neumeier, 2005, p. 163), CALL as a field still lacks qualitative research on blended learning. There is insufficient information about teachers’ perceptions and the roles they play in these mixed environments, and without an understanding of these features, it is difficult to create new and effective models (Grgurovic, 2010). Research has been conducted comparing learning outcomes in traditional and blended foreign language classes, yet the various sociocultural (external) and psychological (internal) aspects that mediate teachers’ and learners’ transition from face-to-face to online learning, seem to go unexamined (White, 2006). Throughout this paper, therefore, I review literature on the infusion of technology into the curriculum, specifically in relation to blended learning, so as to a) illustrate teachers’ views about blended leaning and their transition from face-to-face to blended/online instruction; and b) discuss ways in which future research might provide an alternative understanding of how language teachers manage the new-work order established by the online learning component present in blended programs.